2007
DOI: 10.1113/expphysiol.2007.039560
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to a hot environment can activate rostral ventrolateral medulla‐projecting neurones in the hypothalamic paraventricular nucleus in conscious rats

Abstract: A major integrative site within the brain for autonomic function is the hypothalamic paraventricular nucleus (PVN). Several studies have suggested that the PVN may be involved in the responses regulating body temperature. Hyperthermia elicits redirection of blood flow from the viscera to the periphery and involves changes in sympathetic nerve activity mediated by the central nervous system. The hypothalamic PVN includes neurones that project to the rostral ventrolateral medulla (RVLM), an important autonomic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Recently, we have found that neurons in the PVN that project to the spinal cord or to the RVLM are among the populations of neurons that are activated when body temperature is increased (9,11). Indeed, the proportion of spinal projecting neurons in the PVN that were activated by hyperthermia was Ͼ 20% and is higher than many stimuli examined to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have found that neurons in the PVN that project to the spinal cord or to the RVLM are among the populations of neurons that are activated when body temperature is increased (9,11). Indeed, the proportion of spinal projecting neurons in the PVN that were activated by hyperthermia was Ͼ 20% and is higher than many stimuli examined to date.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that sympathetic nerves innervating those tissues are connected polysynaptically to the PVN and, thereby, can be influenced by the PVN. In support of a role of the PVN in temperature regulation, we have found that neurons in the PVN projecting to the spinal cord or to the pressor region of the RVLM are activated by an increase in core body temperature (9,11). Thus, these central pathways may contribute to the central thermoregulatory pathways elicited by hyperthermia.…”
mentioning
confidence: 85%
“…Descending projections from the PVN directly target the brain stem, notably the rostral ventrolateral medulla, and the intermediolateral column of the spinal cord. Through these pathways, the PVN regulates changes in systemic sympathetic activity (Shafton et al 1998;Cham and Badoer 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The PVN contains thermoregulatory neurons which project to the rRPa and rostral ventrolateral medulla (rVLM), important autonomic regions, to regulate sympathetic outflows to BAT and contributes to BAT thermoregulation. [43][44][45][46] Possibly, activation of H1 receptors in the PVN may stimulate the sympathetic outflow to rRPa and rVLM, which thus increases BAT thermogenesis. Collectively, this evidence suggests that histamine may increase energy expenditure via its action on H1 receptors in the PVN and POA and stimulate the sympathetic outflows to the rRPa and rVLM, therefore increasing BAT sympathetic activity and thermogenesis (Fig.…”
Section: The Role Of Histamine and H1 Receptors In Energy Expenditurementioning
confidence: 99%